Is This Your Final Answer? Evaluating the Effect of Answers on Good Abandonment in Mobile Search - Williams, Kyle; Kiseleva, Julia; Crook, Aidan; Awadallah, Ahmed; Zitouni, Imed; Khabsa, Madian (The 39th Annual International ACM SIGIR Conference on Research and Development in Information Retrieval (SIGIR 2016)., 2016)
Answers on mobile search result pages have become a common way to attempt to satisfy users without them needing to click on search results. Many different types of answers exist, such as weather, flight and currency answers. Understanding the effect that these different answer types have on mobile user behavior and how they contribute to satisfaction is important for search engine evaluation. We study these two aspects by analyzing the logs of a commercial search engine and through a user study. Our results show that user click, abandonment and engagement behavior differs depending on the answer types present on a page. Furthermore, we find that satisfaction rates differ in the presence of different answer types with simple answer types, such as time zone answers, leading to more satisfaction than more complex answers, such as news answers. Our findings have implications for the study and application of user satisfaction for search systems.